Facilitators and barriers to the introduction of atrial fibrillation screening in primary care: a qualitative descriptive study of general practitioners in primary care - Aileen Callanan; Farshid Bayat; Diarmuid Quinlan; Patricia M Kearney; Claire M Buckley; Susan M Smith; Colin P Bradley (James Cook University, 2023)
Introduction: Atrial fibrillation (AF), the most common cardiac arrhythmia, is a major risk factor for stroke. AF is often asymptomatic and, if identified, treatment can be offered that can reduce stroke risk by up to two thirds. AF screening meets many of the Wilson Jungner criteria for screening. While AF screening is recommended in clinical practice and internationally, the optimal mode and location for AF screening remains under investigation. Primary care has been identified as a potential setting. This study aimed to identify facilitators and barriers to AF screening from the perspective of GPs.Methods: The study adopted a qualitative descriptive design conducted in the south of Ireland. 58 GPs were invited from the north Cork region to participate in individual interviews at their practices, rural and urban, with a view to recruiting a purposive sample of up to 12 GPs. The interviews were audio-recorded, transcribed verbatim and analysed using a framework analysis.Results: Eight GPs (four male, four female) from five practices participated. Five GPs were from urban practices and three were from rural practices. Facilitators and barriers were sub-categorised into patient facilitators, practice facilitators, GP facilitators, patient barriers, practice barriers, GP barriers, attitudes to AF screening, willingness to facilitate and priority ranking. All eight participants expressed a willingness to engage in AF screening. Time was the barrier discussed most frequently by all participants along with the need for additional staff. Programme structure was the most discussed facilitator by all participants and patient awareness campaigns.Discussion: Despite barriers to AF screening identified by GPs, there was a significant willingness to engage and identify potential facilitators to support such screening.